Hypocaloric diet and phyto-substance supplement in Non Alcoholic Fatty Liver Disease - Nasti, Gilda; Muscariello, Espedita; Mastantuono, Teresa; Di Maro, Martina; Battiloro, Laura; Vicedomini, Lucia; Grumiro, Daniele; Colantuoni, Antonio (Progress in Nutrition, 2014)
Aim: This study was aimed to evaluate the effects of phyto-substance supplement on hepatic functions in NAFLD patients. Methods: 78 patients, affected by NAFLD, were recruited: group D (39 peoples, 26 females), treated with hypocaloric and hypolipidic diet, and group K (39 peoples, 23 females), administered with hypocaloric and hypolipidic diet and supplement. Anthropometric measurements, serum glucose, total and LDL cholesterol, triglycerides (TG), gamma-GT and hepatic transaminases (AST, ALT) were evaluated before and after six month treatment. Bioimpedance analysis and liver ecography were performed. Finally, hepatic steatosis index (HSI) was calculated. Results: Six months of hypocaloric and hypolipidic diet associated with phyto-substances resulted in a significant reduction of Hepatic Steatosis Index (HSI) in K groups. HIS, indeed, was reduced by 4,4 ± 0,3% in the severely affected patients. On the other hand, the HSI reduction was by 1,6 ± 0,1% in the severely affected patients administered with hypocaloric and hypolipidic diet. Conclusions: Hypocaloric and hypolipidic diet associated to phyto-substance supplement has been proven more useful than only hypolipidic diet in NAFLD patients, facilitating improvement in nutritional status and hepatic metabolism.